Development of a 21-miRNA Signature Associated With the Prognosis of Patients With Bladder Cancer - Yin, Xiao-Hong; Jin, Ying-Hui; Cao, Yue; Wong, York; Weng, Hong; Sun, Chao; Deng, Jun-Hao; Zeng, Xian-Tao (Frontiers in Oncology, 2019)
Objective: To develop a prognostic signature for patients with bladder cancer. Methods:We firstly identified differentially expressed miRNAs between normal bladder tissue and bladder cancer in the TCGA-BCLA dataset, and evaluated the prognostic values of these miRNAs. Then, based on the results of Cox proportional hazards regression model,a 21-miRNA signature was constructed. Furthermore, functional enrichment analyses were conducted to explore the potential effects of the target genes of these 21 miRNAs. Results: 76 differentially expressed miRNAs were identified, among which 21 miRNAs including hsa-let-7c, mir-143, mir-944, mir-192, mir-590, mir-490, mir-141, mir-93, mir-1-2, mir-200c, mir-133a-1, mir-1-1, mir-133b, mir-20a, mir-185, mir-19a, mir-19b-2, mir-19b-1, mir-17, mir-15a, mir-133a-2 were demonstrated to be significantly correlated with the overall survival of bladder cancer patients by using Kaplan-Meier survival analysis and Log-rank test. The results of Chi-square test and multivariable logistic regression analysis showed that the 21-miRNA signature was significantly associated with the diagnosis type and T stage of bladder cancer. Apart from that, univariate and multivariable survival analyses indicated that the 21-miRNA signature was an independent factor in predicting the overall survival of patients with bladder cancer. The results of the functional enrichment analysis suggested that the target genes of these 21 miRNAs were mostly enriched in critical cancer-related biological processes and pathways, and the PPI network suggested that 60 targeted genes interacted with a minimum of 30 genes were at the hub of the whole network. Conclusion: We introduced a 21-miRNA signature which was associated the prognosis of patients of bladder cancer, inspirational ideas for basic and clinical exploration in the future.